马来西亚历史街区的多语文化景观调查研究——以吉隆坡茨厂街为例 - Chong Pei Qi; Ting Hie Ling; Chong Ni Pei; On Yee Min (Universitas Negeri Malang, 2022)
马来西亚多族群、多文化、多宗教相融合的特点决定了马来西亚多语文化的景观。本文选取马来西亚唐人街区中最具代表性的茨厂街作为研究对象，通过实地调查和访谈对多语文化景观进行考察和分析。研究发现，茨厂街形成了以马来语主导，汉、英等多语共存的语言景观。马来语的高突显度即显示马来西亚官方语言的地位象征，也反映了历史街区对多语文化的包容性。本文旨在探讨茨厂街多语文化景观，并对其构成原因进行分析和解读。 The integration of Malaysia's multi-ethnic, multi-cultural, and multi-religious determines the landscape of multilingual culture in Malaysia. The most representative Petaling Street in Malaysia's Chinatown district was selected as the research object in this article, and the multilingual cultural landscape was investigated and analyzed through field investigations and interviews. The study found that Petaling Street has formed a language landscape dominated by Malay and multilinguals such as Chinese and English coexist. The high prominence of Malay not only showed the status symbol of Malaysia's official language, but also reflected the tolerance of multilingual culture in the historical district. This article aimed to explore the multilingual cultural landscape of Petaling Street and analyzed and interpreted the reasons for its composition.